Peningkatan Motivasi Belajar Melalui Penggunaan Media Pembelajaran Permainan Ular Tangga Dalam Mata Pelajaran IPS Di Kelas IV SDN 2 Cijulang (Penelitian Tindakan Kelas Pada Pembelajaran IPS di Kelas IV SDN 2 Cijulang) - Nurlaeli, Fathi; Pratama, Febri Fajar; Mahendra, Hatma Heris (Journal Of Dehasen Educational Review, 2024)
This research was motivated by the low learning motivation of students in class IV social studies at SDN 2 Cijulang. This is due to the lack of varied learning media. The aim of this research is to describe learning planning, learning implementation and increasing learning motivation using the snake and ladder game as media. The research method used was the classroom action research (PTK) method with the research subjects being class IV students at SDN 2 Cijulang. Based on the results of research using the snakes and ladders game media, it shows that the use of the snakes and ladders game media can increase students' learning motivation. This can be seen from the average value of students' learning motivation at the beginning of the pre-action of 18.18%. After using the snake and ladder game media in cycle I, there was an increase of 36.36% and the average score of students in cycle II was 77.27%. So the increase from cycle I to cycle II was 40.91%. This snake and ladder game media is recommended for use in increasing students' learning motivation.